Omalizumab for Urticarial Vasculitis: Case Report and Review of the Literature - Misbah Nasheela Ghazanfar; Simon Francis Thomsen (Case Reports in Dermatological Medicine)
Urticarial vasculitis is characterised by inflamed itching or burning red patches or wheals that resemble urticaria but persist for greater than 24 hours. It is often idiopathic but is sometimes associated with collagen-vascular disease, particularly systemic lupus erythematosus. Treatment options include oral antihistamines, oral corticosteroids, dapsone, colchicine or hydroxychloroquine. We describe a male patient with urticarial vasculitis who was treated with omalizumab (anti-IgE) with convincing results and provide a review of previous reports of patients with urticarial vasculitis treated with omalizumab.